2018
DOI: 10.7249/rr2580
|View full text |Cite
|
Sign up to set email alerts
|

Violent and Antisocial Behaviours at Football Events and Factors Associated with these Behaviours: A rapid evidence assessment

Abstract: is a not-for-profit research organisation that helps to improve policy and decision making through research and analysis. RAND's publications do not necessarily reflect the opinions of its research clients and sponsors. Limited Print and Electronic Distribution Rights This document and trademark(s) contained herein are protected by law. This representation of RAND intellectual property is provided for noncommercial use only. Unauthorized posting of this publication online is prohibited. Permission is given to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 20 publications
(29 reference statements)
1
18
0
2
Order By: Relevance
“…For sporting events, it is important to consider the number of fans without tickets to the actual match who will congregate in public areas. This was a key finding from an evidence review produced as part of this research study (Strang et al 2018). CBM can be used to simulate the accumulation of fans around stadiums or in 'fan zones' and trial different arrangements to minimise the interaction between rival fan groups and law enforcement.…”
Section: Using Outputs From Crowd Modellingmentioning
confidence: 95%
See 2 more Smart Citations
“…For sporting events, it is important to consider the number of fans without tickets to the actual match who will congregate in public areas. This was a key finding from an evidence review produced as part of this research study (Strang et al 2018). CBM can be used to simulate the accumulation of fans around stadiums or in 'fan zones' and trial different arrangements to minimise the interaction between rival fan groups and law enforcement.…”
Section: Using Outputs From Crowd Modellingmentioning
confidence: 95%
“…However, understanding how people will move in space is a vital input to inform policing and crowd management techniques, which in turn might prevent violence and antisocial behaviour. Findings from other parts of this research for Qatar University (Strang et al 2018) have highlighted that separating rival fans, and using screens and 'human corridors' of police officers to guide where spectators move, can be effective management strategies. The research has also found that spatial factors affect crowd behaviour.…”
Section: Using Crowd Behaviour Modelling To Reduce and Prevent Violenmentioning
confidence: 98%
See 1 more Smart Citation
“…It sits alongside two literature reviews conducted as part of the wider study: the first examined violent and antisocial behaviour at football matches and the factors associated with such behaviour (Strang et al 2018) and the second focused on interventions to reduce violent and antisocial behaviour at football matches (Taylor et al 2018). The evidence presented in these two reviews was predominantly based on research conducted in European countries; relatively few studies were identified relating to the Middle East and North Africa (MENA) region.…”
Section: Introductionmentioning
confidence: 99%
“…Rather than searching for specific factors such as those identified in the other evidence reviews conducted as part of this study (Strang et al 2018;Taylor et al 2018), search terms were kept broad and open. They were applied to databases in both English and Arabic (see the back page of this case study for more information on the search strategy).…”
Section: Introductionmentioning
confidence: 99%